Positivized youth in Buenos Aires: class, moral and esthetics in the production of contemporary youths - Fuentes, Sebastián (Última Década, 2019)
The representations, narratives and images on “educated”, religious, generous and sportyyoung individuals, produce a positivization of youth, where discursive formations intersecting and maintaining unequal class and age relationships are generated. Classand age relationships are modeled through images of privileged young people, incontrast to refused, and negativized young individuals from working class areas. Acartography of cultural production in moral terms is carried out, based on anethnographic research among young university students. The moral and marketingdiscursive formations define the current juvenilization of the process of capitalistlegitimization, with young individuals as consumers, and as a mark of both “sales” anddistinction, key aspects for the creation or expansion of markets and estheticpositivization.